PLD.33 Intrapartum antibiotic prophylaxis against early onset Neonatal Group B Streptococcal (GBS) sepsis in women known to be colonised; how good are we?. (9th June 2014) - Breen, H; Costa, J
Abstract : Objectives: Evaluate practice in tertiary care obstetric unit on the prevention of early-onset neonatal GBS disease. Background: The single most important risk factor for early-onset GBS infection is maternal colonisation leading to fetal exposure to GBS during labour. The transmission of GBS from mother to fetus can be reduced with the use of intrapartum antibiotic prophylaxis (IAP). The RCOG guideline recommends offering IAP to all women identified through risk based bacteriological screening. Methods: 212 pregnant women colonised with GBS during the index pregnancy were identified through the lab registry and their labour and delivery details were obtained through Maternity Database. Further information was collected through chart review. Results: Total of 325 vaginal swabs were positive for GBS colonisation in 212 pregnant women during the one-year period from January to December 2012. 10 were lost for follow up and 5 had Caesarean sections leaving 197 women eligible for IAP. GBS status was not known in18 and 2 had quick deliveries. Further 14 did not receive IAP with no identifiable reason leaving only 82.7% of eligible women (163/197) receiving IAP. Out of 14 women who did not receive IAP, 8 had no GBS sticker on the notes and 5 had no results attached to the notes. Conclusions: This study highlights the substandard care for women colonised with GBS. When identified, GBS sticker should be attached to the maternity notes and every effort should be made to identify women's GBS status early in labour in order to offer IAP for all eligible women. References: Stephanie J, Schrag, Sara Zywicki, Monica M. Farley, Arthur L. Reingold, Lee H. Harrison, Lewis B. Lefkowitz, James L. Hadler, Richard Danila, Paul R. Cieslak, Anne Schuchat. Group B streptococcal disease in the era of intrapartum antibiotic prophylaxis. N Engl J Med 2000;342:15–20 Royal College of Obstetricians and Gynaecologists. Green top Guideline No 36, The Prevention of Early-onset Neonatal Group B Streptococcal Disease July 2012